Short note on observation of breeding activities of the lander horseshoe bat (Rhinolophus Landeri- martin, 1837) within an urban area in southwest, Nigeria (2022)
This study made observations on breeding activities of the Lander Horseshoe bat in southwest, Nigeria. Bats were captured using mist nets placed in the ground storey at the University of Ibadan, southwest, Nigeria. Forty-two per cent of total R. landeri (n=14) captured in March, 2017 and between February-August, 2019 were breeding either pregnant or with pups. Though distribution of the species is believed to range nationwide, the last report on breeding activity was about forty-six years ago and with a data deficient status; this observation is the first record for the breeding activities of R. landeri on the southwest range of